Assessment of Image Quality and Lesion Detectability With Digital PET/CT System - Delcroix, Olivier; Bourhis, David; Keromnes, Nathalie; Robin, Philippe; Le Roux, Pierre-Yves; Abgral, Ronan; Salaun, Pierre-Yves; Querellou, Solène (Frontiers in Medicine, 2021)
purpose The aim of this study was to compare the overall image quality and lesion detectability between four Positron Emission Tomography (PET) datasets using a digital Biograph Vision PET/Computed Tomography (CT) system. Material and methods Consecutive patients who underwent a FDG PET/CT during the first week of use of the digital PET/CT Biograph Vision at our center were analyzed. PET was realized using list mode acquisition. For all patients, four datasets were reconstructed. We defined, as reference, an equivalent time acquisition/reconstruction parameters pair of the digital PET/CT corresponding to an analog PET/CT image quality (‘analog-like’). We evaluated three others dedicated digital PET/CT reconstruction parameters, allowing a decrease of emission duration: 60, 90 and 120 seconds per bed position. Three nuclear medicine physicians evaluated independently, for each dataset, overall image quality (Maximal Intensity Projection (MIP), noise, sharpness and artifact) using a 4-point scale. Physicians assessed also lesion detection capability by reporting new visible lesions on each digital datasets with their confidence level in comparison with analog-like dataset. Differences were considered significant for a p value  0.05. Results Ninety-eight patients were analyzed. Image quality of MIP (IQMIP), sharpness (IQSHARPNESS) and noise (IQNOISE) of all digital datasets (60, 90 and 120 seconds) were better than those evaluated with analog-like reconstruction. IQMIP, IQNOISE and IQSHARPNESS improvements were higher for patients with a Body Mass Index (BMI)  25kg/m2. No improvement was observed for IQARTIFACT between digital and analog-like datasets. Lesion detection capability and confidence level were higher for 60, 90, 120 seconds per bed position, respectively, than for analog-like images. Conclusion The use of digital PET/CT improves image quality, increases lesion detectability and outperforms analog PET/CT for MIP, sharpness and noise.